Malaria control as part of primary health care : report of a WHO study group, meeting held in Geneva from 21 to 29 November 1983 - WHO Study Group on Malaria Control as Part of Primary Health Care; World Health Organization (Geneva : World Health Oraganization, 1984)
The report that signalled the move away from time-limited malaria control campaigns towards a more integrated, ongoing attack on malaria. Emphasis is placed on ways in which the primary health care approach can be used to improve the effectiveness and efficiency of malaria control programmes. Sections cover actions that can be taken at the local level, action in collaboration with other sectors, and the changes needed to transform a vertical service into an integrated health system based on primary health care. Other ections identify supportive activities for the use of anti-malaria drugs and assess problems in manpower development.
Introduction -- 1. Antimalaria action at the community (local) Level -- 2. Role of health services in the support of antimalaria action -- 3. Human resource development for antimalaria action -- 4. Intersectoral action -- 5. Strengthening health infrastructure for malaria control through primary health care -- 6. Areas of research -- 7. guidelines for antimalaria action in the context of primary health care -- 8. Recommendations -- Acknowledgements -- Annexes
Keywords: Malaria; Primary Health Care